PENERAPAN TEKNOLOGI CACHE SERVER BERBASIS IoT DENGAN RASPBERRY Pi3 MENGGUNAKAN METODE FORWARD CHAINNING - Subandri Subandri; Sabar Hanadwiputra (Sekolah Tinggi Teknik - PLN, 2018)
With the rapid technological development, the growing number of Internet clients over time, the internet access response is slow and it takes filtering of a few websites that can harm users. For that required cache proxy server to speed up internet access time and website filtering. The use of proxy servers usually still use the standard configuration on the proxy server. This configuration can be set or modified (tuning) in such a way as to create a proxy server that is reliable and have better performance. The play on the proxy server is done by changing some parameters that are inside the proxy server application and adapted to the needs of usage on the internet network. The application used to create this proxy server is squid that runs on raspberry pi3 with a rasbian operating system. Squid applications are mostly used in local and internet networks for storing web cache, blocking multiple websites, managing bandwidth up to access restrictions.